2006
DOI: 10.1111/j.1365-2443.2006.00927.x
|View full text |Cite
|
Sign up to set email alerts
|

Human T‐cell leukemia virus type‐I oncoprotein Tax inhibits Fas‐mediated apoptosis by inducing cellular FLIP through activation of NF‐κB

Abstract: Human T-cell leukemia virus type I (HTLV-I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 41 publications
6
76
0
Order By: Relevance
“…Although the role of c-FLIPL is controversial, c-FLIPS has been shown to be antiapoptotic and confers resistance to Fas-mediated apoptosis by blocking the proteolytic activation of caspase-8 in T lymphocytes [18][19][20][21][22][23]. Indeed, studies have shown that c-FLIPS plays a major anti-apoptotic role and prevents Fas-mediated apoptotic death in adult T leukemia and lymphoma cells [18,23,[31][32][33][34]. Our data showed that MAT II inhibition down-regulates c-FLIPS expression in a dose-dependent manner and reinstates Fas-mediated apoptotic signaling and cell death in T leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of c-FLIPL is controversial, c-FLIPS has been shown to be antiapoptotic and confers resistance to Fas-mediated apoptosis by blocking the proteolytic activation of caspase-8 in T lymphocytes [18][19][20][21][22][23]. Indeed, studies have shown that c-FLIPS plays a major anti-apoptotic role and prevents Fas-mediated apoptotic death in adult T leukemia and lymphoma cells [18,23,[31][32][33][34]. Our data showed that MAT II inhibition down-regulates c-FLIPS expression in a dose-dependent manner and reinstates Fas-mediated apoptotic signaling and cell death in T leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of lentiviral vectors. Constructs expressing shRNAs against mouse ERK7 were generated by subcloning the silencing oligonucleotides into the ApaI/ EcoRI site of the CSII-U6-MCS-EGFP vector, which was designed to coexpress shRNA and the EGFP reporter 50 . The sequences of the silencing oligonucleotides were as follows: ERK7 shRNA no.…”
Section: Methodsmentioning
confidence: 99%
“…Constructs expressing shRNAs against mouse Mab21-l3 (mMab21-l3 shRNAs) were generated by subcloning the silencing oligonucleotides into the ApaI/EcoRI site of the CSII-U6-MCS-EGFP vector, which was designed to co-express shRNA and the enhanced green fluorescent protein (EGFP) reporter 37 . The sequences of silencing oligonucleotides are as follows: mMab21-l3 shRNA #1-sense, 5 0 -AAAGCTACCCACCAGATTTCTC AAGAGAAAATCTGGTGGGTAGCTTTCCTTTTTT-3 0 ; mMab21-l3 shRNA #1-antisense, 5 0 -AATTAAAAAAGGAAAGCTACCCACCAGATTTTCTCTTGA GAAATCTGGTGGGTAGCTTTGGCC-3 0 ; mMab21-l3 shRNA #2-sense, 5 0 -GCA GAAGGTTGCTGCTATACTCTCAAGAGAAGTATAGCAGCAACCTTCTGCT TTTTTTT-3 0 ; and mMab21-l3 shRNA #2-antisense, 5 0 -AATTAAAAAAAAGCA GAAGGTTGCTGCTATACTTCTCTTGAGAGTATAGCAGCAACCTTCTGCG GCC-3 0 .…”
Section: Methodsmentioning
confidence: 99%